Electrochemical fabrication of nanocomposites towards sustainable energy applications - Suominen, Milla (fi=Turun yliopisto|en=University of Turku|, 2019)
In the fight against climate change, effective energy storage applications are required to efficiently store the energy of renewable sources. Supercapacitors are one of the energy storage applications under vigorous research and development. Their ability to store a relatively large amount of energy and release it fast over millions of operating cycles has deemed these devices suitable for electric vehicles, for example. But current technology lacks in energy content which is why a novel category of supercapacitors, hybrid capacitors, has emerged. Hybrid capacitor can consist of a battery type electrode and a capacitor type electrode or both electrodes can be made of composite materials, which are materials composed of two or more individual components. Combining these components in right ratios gives the new composite material altered physico-chemical properties. Several types of composites have been evaluated for use in supercapacitors, and one that has reached a lot of attention are composites between graphene and conducting polymers. The aim of this work has been to fabricate and thoroughly characterize these types of nanocomposites. In general, the large mechanically strong and well-conducting graphene should contribute to the cycling stability and power capability of the material while the conducting polymer should store and release large amount of energy. These nanocomposites can be fabricated by chemical and electrochemical approaches, which are presented in the literature background of this thesis. However, all of these fabrication approaches requires that both materials should be readily available as stable suspensions. The problems and solutions of producing graphene dispersions is therefore discussed in the literature review. In the experimental part of this work a facile electrochemical approach is presented for the formation of composites between reduced graphene oxide and two different types of conducting polymers, poly(3,4-ethylenedioxythiophene) and polyazulene, in various ionic liquids. The approach used in this project is fast and takes advantage of the ionic liquids ability to disperse both the monomers and graphene oxide not to mention the improvement in electroactivity and cycling stability that is obtained by polymerizing conducting polymers in ionic liquids. The as-prepared composite materials have been thoroughly characterized by electrochemistry, spectroscopy, microscopy and spectroelectrochemistry.

Taistelussa ilmastonmuutosta vastaan tarvitaan tehokkaita energianvarastointisovelluksia, joilla voidaan tehokkaasti varastoida uusiutuvista energian lähteistä tuotettu energia. Superkondensaattorit ovat yksi energianvarastointisovelluksista, joita tutkitaan ja kehitetään tarmokkaasti. Niiden kyky vapauttaa suhteellisen suuri määrä energiaa nopeasti ja useiden miljoonien syklien ajan on ominaisuus, josta esimerkiksi sähköautot voivat hyötyä. Mutta kaupalliset sovellukset eivät pysty varastoimaan tarpeeksi energiaa minkä vuoksi on alettu kehittää hybridikondensaattoreita. Hybridikondensaattori voi koostua paristotyyppisestä elektrodista ja kondensaattorityyppisestä elektrodista tai molemmat elektrodit voivat koostua komposiittimateriaalista, jossa kaksi tai useampia materiaaleja on yhdistetty uudeksi materiaaliksi. Kun näitä materiaaleja yhdistetään oikeassa suhteessa toisiinsa, uuden komposiittimateriaalin ominaisuudet ovat huomattavasti erilaiset kuin yksittäisten komponenttien ominaisuudet. Monenlaisten komposiittien ominaisuuksia superkondensaattoreissa on tutkittu ja yksi paljon huomiota saanut komposiittityyppi ovat grafeenin ja johdepolymeerien muodostamat materiaalit. Yleisesti ottaen mekaanisesti kestävä ja hyvin johtava grafeeni takaa pitkän eliniän ja nopean energian varastoinnin ja vapautuksen kun taas johdepolymeerin tehtävänä on varastoida suuri määrä energiaa. Näitä komposiitteja voidaan valmistaa useilla eri menetelmillä kuten kemiallisella polymerisaatiolla ja sähkökemiallisilla menetelmillä, joita käydään läpi tämän työn kirjallisuusosiossa. Kaikkien valmistusmenetelmien reunaehto kuitenkin on, että molempien materiaalien tulee muodostaa pysyviä seoksia useissa liuottimissa. Pysyvien grafeeniseosten aikaansaaminen on kuitenkin hankalaa ja mahdollisia keinoja pysyvien grafeeniseosten valmistamiseen käydään läpi työn kirjallisuusosiossa. Työn kokeellisessa osiossa esitellään yksinkertainen sähkökemiallinen menetelmä, jossa valmistetaan komposiitteja pelkistetystä grafeenioksidista ja johdepolymeereista (poly(3,4-etyleenidioksitiofeeni) ja polyatsuleeni) ionisissa nesteissä. Tässä työssä käytetty menetelmä hyödyntää ionisten nesteiden kykyä liuottaa sekä johdepolymeerien monomeerejä että grafeenioksidia sekä niiden kykyä muodostaa sähkökemiallisesti aktiivisempia ja pysyvämpiä johdepolymeerikalvoja. Valmistetut komposiittimateriaalit on huolellisesti karakterisoitu sähkökemiallisin, spektroskooppisin, mikroskooppisin ja spektrosähkökemiallisin menetelmin.